7x+2x-3x=3(x-8)

Simple and best practice solution for 7x+2x-3x=3(x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+2x-3x=3(x-8) equation:


Simplifying
7x + 2x + -3x = 3(x + -8)

Combine like terms: 7x + 2x = 9x
9x + -3x = 3(x + -8)

Combine like terms: 9x + -3x = 6x
6x = 3(x + -8)

Reorder the terms:
6x = 3(-8 + x)
6x = (-8 * 3 + x * 3)
6x = (-24 + 3x)

Solving
6x = -24 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
6x + -3x = -24 + 3x + -3x

Combine like terms: 6x + -3x = 3x
3x = -24 + 3x + -3x

Combine like terms: 3x + -3x = 0
3x = -24 + 0
3x = -24

Divide each side by '3'.
x = -8

Simplifying
x = -8

See similar equations:

| y=2(3)-25 | | .01(900-30x)=9.8x+400 | | 3x^2=288x^2 | | 9+5w-14x=12-6w | | y=3(3)-22 | | 5(2x+6)=4(-5-2x)3x | | x-4=-4x-2 | | 4m-19-11=70 | | 6r-18=30 | | 18=-3y-12 | | 87-x=136 | | 3/8=r2/3 | | (3w+5x-7)(w+7x)= | | X+5=x+11 | | 5x+4x+8-2x-8= | | 4/17 | | y=-5(3)+17 | | 2=(4/p) | | 4(6-4+6)= | | 5x-4=4-4x | | 8+8x=4x+24 | | 3(2z+2.5)-2(2-1)=78 | | (2/3)(-11/8) | | -48+3m=-6(1-4m) | | ln(4x^2-100)-ln(x-2)=0 | | -2p+3=8p-7 | | 9c-3=15c+15 | | 12h+2h-3=5h+1+h | | 2x+5x+20=3x | | (2/3)(-11/8), | | -27+20e=73 | | .05x+150=2500 |

Equations solver categories